Title: Jealous protons sour another happy marriage; the story of how TRPV5 and PI(4, 5)P2 split up. (July 2022) - van Goor, Mark K.C.; van der Wijst, Jenny; Hoenderop, Joost G.J.
Highlights: Acidification causes PI(4, 5)P2 dissociation from TRPV5 and inhibits calcium reabsorption. Protein kinase A structurally competes with the calmodulin binding site on TRPV5 to prevent calcium-dependent channel inhibition. Abstract: TRPV5 is a highly selective calcium channel that finetunes urinary calcium excretion by reabsorbing calcium from the pro-urine. New structural findings show how PTH and pH control TRPV5 activity by altering the binding of endogenous ligands calmodulin and phosphatidylinositol 4, 5-bisphosphate (PI(4, 5)P2 ). Graphical abstract: Image, graphical abstract